Institucionalização e adoção, à luz da teoria Bowlbyana do apego e da carta de Paulo a Filemom - Silva, Mauro Luiz Ferreira (2014)
This dissertation is a study of institutionalization and adoption of children. It is divided into four chapters. In the first, the author exposes the causes and types of institutionalization, the legal process of adoption and its obstacles. The second and third chapters constitute the core of this research; the second is focused on the theory of the mother-child bond, the possibility of replacing the natural bond, and the effects of not bonding the child to a specific figure. There, our main reference is the psychiatrist and psychoanalyst John Bowlby. In the third chapter we find, through the Pauline pen, specially through his Epistle to Philemon, the theological foundation for the practice of adoption and protest in favor of institutionalized children. In the fourth and final chapter we analyze some stories of adoption, the effects of which counterpose the psychic damage of institutionalization.